A Contemporary Retrospective Study of Survival in Dogs With Primary Lung Tumors: 40 Cases (2005–2017) - Rose, Ruth J.; Worley, Deanna R. (Frontiers in Veterinary Science, 2020)
Objective: To report the median survival time in a contemporary cohort of dogs with primary lung tumors and intrathoracic nodal metastasis. Design: Retrospective Case Series Animals (or sample): Dogs with primary lung tumors treated with lung lobectomy and lymph node biopsy Procedures: The medical record database at Colorado State University was queried for dogs with primary lung tumors from January 1, 2005 to December 31, 2017. Patients were identified for inclusion if they had lung lobectomy and an intrathoracic lymph node biopsy performed. The median survival time (MST) for lymph node positive (LN+) and negative dogs (LN-) was calculated as well as the MST in dogs that did or did not receive adjuvant chemotherapy. Differences were compared between groups with significance set at p<0.05. Results: The MST in LN+ dogs (n=11) was 167 days which was not statistically different from LN- dogs (n=29) at 456 days (p=0.2407). No significant difference in the MST in LN+ dogs was identified between dogs that received adjuvant chemotherapy (n=4; 110 days) and those that did not receive adjuvant chemotherapy (n=6; 125 days) (p= 0.4409). There was no difference in survival time in LN- dogs receiving chemotherapy (n=12; 335 days) as compared to those LN- dogs (n=10) that did not receive adjuvant chemotherapy (258.5 days; p=0.6475). Conclusions and Clinical Relevance: The survival of primary pulmonary neoplasia in dogs with intrathoracic nodal metastasis is longer than previously reported in this contemporary cohort. Chemotherapy did not appear to improve survival in LN+ or LN- dogs. The combination of tumor size between 100 and 999cm3 and positive lymph node status significantly reduced survival.